Progress and perspectives on BMP9-ID1 activation of HIF-1α and VEGFA to promote angiogenesis in hepatic alveolar echinococcosis - Ke, Fei; Xu, Meng-Zhao; Ma, Long; Chen, Qi-Dong; He, Bei-Bei; A, Ji-De (Frontiers in Oncology, 2024)
Hepatic alveolar echinococcosis is a zoonotic disease with a high incidence in western China, particularly affecting plateau areas such as Qinghai, Tibet, and Xinjiang. Research has indicated the presence of neovascularization in the peripheral infiltration area of hepatic alveolar echinococcosis, with a strong correlation between angiogenesis and vascular endothelial growth factor A (VEGFA) and hypoxia-inducible factor 1-alpha (HIF-1α) overexpression. Given the similarities between hepatic alveolar echinococcosis and liver cancer, current research is focused on treating the disease by targeting related signaling pathways using molecular drugs used for liver cancer. This article aims to summarize the biological regulation of HIF-1α and VEGFA overexpression in angiogenesis related to hepatic alveolar echinococcosis, as well as the impact of the BMP9-ID1 signaling pathway on the expression levels of HIF-1α and VEGFA, providing new insights for potential treatment strategies.